2017
DOI: 10.1074/jbc.m117.799676
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase 2-mediated phosphorylation of Brahma-related gene 1 controls myoblast proliferation and contributes to SWI/SNF complex composition

Abstract: Transcriptional regulation is modulated in part by chromatin-remodeling enzymes that control gene accessibility by altering chromatin compaction or nucleosome positioning. Brahma-related gene 1 (Brg1), a catalytic subunit of the mammalian SWI/SNF chromatin-remodeling enzymes, is required for both myoblast proliferation and differentiation, and the control of Brg1 phosphorylation by calcineurin, PKCβ1, and p38 regulates the transition to differentiation. However, we hypothesized that Brg1 activity might be regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 79 publications
3
73
0
Order By: Relevance
“…CK2 kinase activity has been described to target members of both the MRF and paired box (Pax)3 and 7 families via either direct phosphorylation or phosphorylation of their transcriptional regulators and protein partners (24)(25)(26)(27)(28)(29)(30)(31) and to be mainly involved in promoting muscle precursor cell proliferation (27,28,(30)(31)(32). However, the role of CK2 in the progression of the myogenic program and skeletal muscle formation is still to be investigated.…”
mentioning
confidence: 99%
“…CK2 kinase activity has been described to target members of both the MRF and paired box (Pax)3 and 7 families via either direct phosphorylation or phosphorylation of their transcriptional regulators and protein partners (24)(25)(26)(27)(28)(29)(30)(31) and to be mainly involved in promoting muscle precursor cell proliferation (27,28,(30)(31)(32). However, the role of CK2 in the progression of the myogenic program and skeletal muscle formation is still to be investigated.…”
mentioning
confidence: 99%
“…Thus, CK2 has been associated with proliferation, lineage determination and differentiation of various tissues, including skeletal muscle [40].Pax7 locus [17]. In addition, phosphorylation of Brg1 by CK2 correlated with the subunit composition of the mSWI/SNF enzyme complex and its sub-nuclear localization [17].Here we report novel findings about Brg1 phosphorylation by CK2. We found that co-localization between CK2 and Brg1 occurred only in cells undergoing mitosis in developing somites of mouse embryos and in primary myoblasts isolated from satellite cells.…”
mentioning
confidence: 53%
“…This suggested that Brg1 is a target of additional signal transduction pathways. Our subsequent studies showed that Brg1 was phosphorylated by casein kinase 2 (CK2), a Serine/Threonine kinase, which promoted myoblast proliferation and survival by regulating subnuclear localization and incorporation of one of two related subunits, BAF155/BAF170, into the enzyme complex [17].CK2 is ubiquitously expressed and functions as a tetramer of two catalytic subunits, CK2α or CK2α', and two CK2β regulatory subunits, and it has more than 300 known substrates [29][30][31].CK2 is required for cell cycle progression, survival, apoptosis, and transcriptional regulation.Knockout mice lacking the CK2α subunit show cardiac and neural tube defects and die during embryogenesis, whereas mice lacking the α' subunit have impaired spermatogenesis [32][33][34].Knockout of the CK2β subunit in mice leads to reduced proliferation during embryogenesis, which is reflected in the small size of the animals at embryonic day 6.5 (E6.5) and resorption at E7.5 [35]. Analyses of a murine conditional knockout model showed that CK2β is essential for viability of embryonic stem cells and primary embryonic fibroblasts [35].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, both PKCβ1 and calcineurin can be localized to myogenic gene promoters in association with Brg1, but in a mutually exclusive, temporally separable manner (115). Recent evidence shows additional regulation of Brg1-mediated chromatin remodeling in proliferating myoblasts by casein kinase 2 (116). Regulation of chromatin remodeling by post-translational modification of subunit proteins indicates that simply targeting remodeling enzymes via interactions with transcription factors is likely an insufficient mechanism to regulate chromatin remodeling activity.…”
Section: The Chromatin State At Active Myogenic Locimentioning
confidence: 99%